Gcg, Profitability And Solvency On Stock Price With Firm Size As Control Variable - Prasayu, Yolanda Argareta; Nuswantara, Dian Anita (International Environmental Conferrence on Biosustainability Advancement, 2024)
Researchers have a goal to determine the effect of GCG (Good Corporate Governance), profitability, solvency on stock prices with company size as a control variable. This study uses annual report data on companies (secondary data). The population used by the researchers were companies that received CGPI ratings and IDX listings for the 2018 – 2021 period. The samples used by the researchers were 6 companies. The purposive sampling method was used by researchers to obtain the sample. Researchers tested the data with the SPSS 23 program. Researchers used multiple linear regression methods in their tests. This study shows the simultaneous results that GCG, profitability, solvency and company size affect the stock price of the company. Partially this study shows the results that profitability, solvency and company size do not affect stock prices, while GCG (Good Corporate Governance) has an effect on company stock prices.